Learning styles and academic performance in the digital era in Peruvian engineering students - Arias-Pittman, José Augusto; Manrique-Quiñonez, Javier Alberto; Espinoza-Morimoto, Manuel; Barrera-Loza, Ana Doris Magdalena (Revista de Ciencias Sociales, 2023)
The main objective of the research is to determine the relationship between learning styles and academic performance, in addition to discriminating the predominant learning style. The research is a descriptive correlational, non-experimental study. The target was the 297 students attending the School of Industrial Engineering and the sample of 233 surveyed. The Honey & Alonso - CHAEA - questionnaire with 20 questions for each style was applied. The questions analysed were those that were answered with a "YES". It was determined that there is a difference between the four styles, - p value (0.0298) < α (0.05) -; and that the reflective and active styles are statistically significantly different; academic performance is related to the four learning styles where the reflective style has the greatest impact with a coefficient of 0.462 followed by the theoretical style with a coefficient of 0.255; using Weka software in Machine Learning, allowed us to reaffirm that the dominant learning style is reflective, which will allow us to guide the actions of teaching and learning. It was demonstrated that there is a relationship between learning styles and academic performance ρ= 0.833 with (1-α) = 0.99.